Perceived role in end-of-life decision making in the NICU affects long-term parental grief response. Issue 1 (25th June 2012) - Caeymaex, Laurence; Jousselme, Catherine; Vasilescu, Caroline; Danan, Claude; Falissard, Bruno; Bourrat, Marie-Michèle; Garel, Micheline; Speranza, Mario
Abstract : Background: Shared decision making (DM) is increasingly advocated as the most appropriate model to support parents confronted with end-of-life (EoL) decisions for a child in the neonatal intensive care unit (NICU). However, few studies have explored its impact on their long-term grief. Objectives: The aim of this study was to investigate whether parental perception of the type of involvement in the EoL decision-making process (EoL DMP) for their child in the NICU is related to their long-term grief outcome. Methods: A retrospective study with mixed methods. The study included parents whose child died from 2002 through 2005 in one of four NICUs in different areas in France, with interviews of 78 individual parents of 53 children, 2.7±0.6 years after the child's death. Parental perception of the type of involvement in the EoL DMP was determined by qualitative analysis of face-to-face interviews and classified as follows: shared, medical, informed parental and no decision. Grief reactions were assessed with the Texas Revised Inventory of Grief (TRIG-F). Results: Current grief scores differed significantly according to the perceived type of EoL DM. Shared DM was associated with lower TRIG-F scores (less grief) than were the other types of EoL DM (F=7.95; p=0.05). The baby's perceived suffering was also associated with higher grief scores (F=6.51, p=0.01). Conclusions: In decisions to forego life-sustaining treatment in the NICU, the perception of a shared decision is associated in the long term with lower grief scores than perceptions of the other types of DM.